2017
DOI: 10.1097/aap.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

Single-Injection Versus Multiple-Injection Technique of Ultrasound-Guided Paravertebral Blocks

Abstract: An ultrasound-guided single-injection PVB provides equivalent dermatomal spread and duration of analgesia compared with a multiple-injection PVB. The single-injection technique takes less time to perform and hence may be preferred over a multiple-injection technique.The trial was registered prospectively at ClinicalTrials.gov (NCT02852421) on July 15, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 33 publications
2
37
0
2
Order By: Relevance
“…While several methods have been previously suggested for USG‐TPVB,, the IC approach is one of the typical examples of the lateral approach, Cowie et al found that the IC approach has a tendency to spread along the relevant intercostal level and that multiple injections are more effective for covering multi‐intercostal segments. Conversely, a recent study suggested that the number of blocked dermatomes in the medial approach passing through SCTL was equivalent between single and multiple injections . Thus, such differences in distribution patterns could affect the analgesic efficacy in this study.…”
Section: Discussionmentioning
confidence: 66%
“…While several methods have been previously suggested for USG‐TPVB,, the IC approach is one of the typical examples of the lateral approach, Cowie et al found that the IC approach has a tendency to spread along the relevant intercostal level and that multiple injections are more effective for covering multi‐intercostal segments. Conversely, a recent study suggested that the number of blocked dermatomes in the medial approach passing through SCTL was equivalent between single and multiple injections . Thus, such differences in distribution patterns could affect the analgesic efficacy in this study.…”
Section: Discussionmentioning
confidence: 66%
“…The efficacy of paravertebral blocks in breast cancer surgery has been reported in four meta‐analyses including 32 studies . Our literature search identified 21 studies over our search period, nine of which were included in those meta‐analyses . The use of thoracic paravertebral blocks resulted in lower postoperative pain scores (p < 0.001) , lower opioid consumption compared with general anaesthesia (relative risk (RR) 0.23; 95%CI 0.15–0.37) and a lower incidence of postoperative nausea and vomiting (RR 0.27; 95%CI 0.12–0.61) compared with a control group receiving systemic analgesia alone.…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies by Renes et al and Marhofer et al have presented evidence of multidermatomal spread, six and four dermatomes, respectively, with dynamic ultrasound‐guided PVB using a single injection with 20 ml of local anaesthetic. Furthermore, both single‐ and multilevel ultrasound‐guided PVB have been shown to achieve similar dermatomal spread, according to a recent study . Ultrasound‐guided injection in the paravertebral space can achieve a wide spread, even to other anatomically continuous areas, including the epidural space, the contralateral paravertebral space and multilevel paravertebral space .…”
Section: Ultrasoundmentioning
confidence: 92%
“…The ultrasound‐guided technique reliably achieves spread to the paravertebral space, even with small volumes (1 ml) injected in the intercostal space, according to a cadaver study . Radiographic, clinical and cadaveric studies indicate that a single‐level dynamic ultrasound‐guided PVB consistently produces multidermatomal block and extensive cranio‐caudal spread . For example, studies by Renes et al and Marhofer et al have presented evidence of multidermatomal spread, six and four dermatomes, respectively, with dynamic ultrasound‐guided PVB using a single injection with 20 ml of local anaesthetic.…”
Section: Ultrasoundmentioning
confidence: 98%